The Office Survival Pack: Realistic Strategies for Surviving and Winning in an Uncertain Workplace - Salam, Rudi (Jurnal Ad'ministrare: Jurnal Pemikirian Ilmiah dan Pendidikan Administrasi Perkantoran, 2025)
This study addresses the critical challenge of maintaining Workplace Resilience among Indonesian employees facing unprecedented market volatility and technological disruption, an issue underscored by global reports (WEF, 2024). Although existing theory supports Dynamic Capabilities at the organizational level (Teece, 2018) and Psychological Capital (Luthans, 2020) at the individual level, a significant gap remains in providing practical coping strategies relevant to Indonesia’s specific local work dynamics. The research adopted a qualitative-exploratory approach, utilizing in-depth interviews with 18 High Performers (HiPo) in the Indonesian MNC and startup sectors, with the aim of formulating and validating an evidence-based conceptual model: "The Office Survival Pack." Thematic analysis revealed that this Survival Pack consists of three integrated dimensions: Cognitive Resilience (characterized by the 'Controllable Focus' strategy), Emotional-Behavioral Resilience (driven by 'Micro De-escalation Strategies' for real-time stress management), and Relational Resilience (involving informal 'Professional Mentoring Hubs'). The findings demonstrate that these strategies were developed by individuals to fill the void left by generic organizational support, thus the structured Survival Pack model provides realistic strategic guidance for employees to move from merely surviving to excelling amidst workplace uncertainty.